Validation of a Reversed-Phase High Performance Liquid Chromatography Method for the Simultaneous Analysis of Cysteine and Reduced Glutathione in Mouse Organs. (17th January 2016) - Brundu, Serena; Nencioni, Lucia; Celestino, Ignacio; Coluccio, Paolo; Palamara, Anna Teresa; Magnani, Mauro; Fraternale, Alessandra
Abstract : A depletion of reduced glutathione (GSH) has been observed in pathological conditions and in aging. Measuring GSH in tissues using mouse models is an excellent way to assess GSH depletion and the potential therapeutic efficacy of drugs used to maintain and/or restore cellular redox potential. A high performance liquid chromatography (HPLC) method for the simultaneous determination of GSH and cysteine (Cys) in mouse organs was validated according to USA and European standards. The method was based on separation coupled with ultraviolet detection and precolumn derivatization with 5, 5′-dithiobis-(2-nitrobenzoic acid) (DTNB). The required validation parameters, that are, selectivity, linearity, lower limit of quantification, precision, accuracy, recovery, and stability, were studied for spleen, lymph nodes, pancreas, and brain. The results showed that the lower limits of quantification were 0.313 μ M and 1.25 μ M for Cys and GSH, respectively. Intraday and interday precisions were less than 11% and 14%, respectively, for both compounds. The mean extraction recoveries of Cys and GSH from all organs were more than 93% and 86%, respectively. Moreover, the stability of both analytes during sample preparation and storage was demonstrated. The method was accurate, reliable, consistent, and reproducible and it was useful to determine Cys and GSH in the organs of different mouse strains.